Impact of financial distress and CSR on the market value of the property sector - Bahrul Yaman; Muhamad Rivo Andriansyah; Bisri Bisri; Eris Sudariswan (Enrichment : Journal of Management, 2023)
The property and real estate construction sector became one of the sectors with very rapid growth in share value. However, the construction sector fell in value when the pandemic hit due to many projects not working. The importance of studying financial distress and CSR on the market value of property companies as a management decision in going through critical times. This study aims to analyze the influence of Financial Distress (FD), Corporate Social Responsibility (CSR), Price to Book Value (PBV), and Firm Value (Size Firm/Total Assets) on the Market Value of Equity (MVE). The financial distress variable is used to see the company's financial condition, and this study shows that Financial Distress does not affect the Market Value of Equity. Corporate Social Responsibility is used to the extent that the company fulfills its social obligations and, in this study, has an influence on the Market Value of Equity. to see the company's value, use price to book value. In this study, Price to Book Value influences the Market Value of Equity. Firm value (Total Assets) is used as a comparison of inter-company value, and in the research, firm value does not affect the Market Value of Equity. Financial Distress, Corporate Social Responsibility, Price Book Value, and firm value simultaneously influence.